Mixed farming systems initiative enhances productivity and resilience in Nepal’s hill agriculture - International Water Management Institute (International Water Management Institute, 2025)
In Nepal’s middle hills, small landholdings and challenges like limited irrigation, transportation, and market access have long hindered commercial farming and mono-cropping. However, mixed farming remains a resilient and sustainable solution for these communities. Through the CGIAR Initiative on Mixed Farming Systems (MFS), IWMI, in collaboration with International Maize and Wheat Improvement Center (CIMMYT) and research and implementation partners, has been working to intensify sustainable agriculture in pilot areas. As a result, farmers are now diversifying risks, optimizing labour, and increasing productivity—all while preserving the environment. The initiative has also introduced socio-technical innovations tailored for women and elderly farmers, strengthened entrepreneurship skills among female and smallholder farmers, and fostered stronger networks among diverse farming groups. These interventions have made farming in Nepal’s hills more sustainable, efficient, and inclusive, and with promising results, have demonstrated potential to scale.